Answer:
$ 5674.076
Step-by-step explanation:
The question is on compound interest
The formulae = A= P(1+ r/n) ^nt .......where P is the principal amount, r is the rate of interest in decimal, n is number of compoundings per year and t is the total number of years.
Given; P= $4,000.00 , r=12/100=0.12, n=2 and t=3
Substituting values in the equation A= P(1+ r/n) ^nt
A= 4000 ( 1+0.12/2)^2×3
A=4000(1.06)^6
A=$ 5674.08
Answer:
Jim's current weight = 119 pounds
Step-by-step explanation:
1 Stone = 14 pounds
stone = 1.5 stone
1.5 stone = 1.5 (14 pounds) = 21 pounds
Jim lost 21 pounds
Let X be Jim's Original Weight
Y be his present weight
As per given statement in the Question:
After losing 1.5 stones (21 pounds of weight) Jim now weighs Y
Present weight = original weight - 21
Y = X -21 <u> Equation 1</u>
Also Current Weight = 85 % (Original weight)
Y = 85 % (X) =![\frac{85X}{100}](https://tex.z-dn.net/?f=%5Cfrac%7B85X%7D%7B100%7D)
Y=![\frac{85X}{100}](https://tex.z-dn.net/?f=%5Cfrac%7B85X%7D%7B100%7D)
put in Equation 1
= X-21
85X = (X-21) 100
85 X = 100 X -2100
or
2100 = 100 X - 85X
2100 = 15X
or
15 X = 2100
![X=\frac{2100}{15}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B2100%7D%7B15%7D)
X= 140 pounds ( Original Weight)
Current Weight = Y = Original weight - 21 <u><em>(From Equation 1)</em></u>
Y = X -21
Y = 140 -21
Y = 119 pounds (Current Weight)
Answer:
Option D. 11√6/2
Step-by-step explanation:
We'll begin by calculating the side opposite to angle 60°.
This is illustrated below:
Angle θ = 60°
Opposite =?
Hypothenus = 11
Using the sine ratio, we can obtain the side opposite to angle 60° as follow:
Sine θ = Opposite/Hypothenus
Sine 60 = Opposite /11
Cross multiply
Opposite = 11 × Sine 60
Sine 60 = √3/2
Opposite = 11 × √3/2
Opposite = 11√3/2
Finally, we shall determine the value of x as follow:
Angle θ = 45°
Opposite = 11√3/2
Hypothenus = x
Using the sine ratio, we can obtain the value of x as shown below:
Sine θ = Opposite/Hypothenus
Sine 45° = 11√3/2 /x
Cross multiply
x × Sine 45° = 11√3/2
Sine 45° = 1/√2
x × 1/√2 = 11√3/2
x/√2 = 11√3/2
Multiply through by √2
x = √2 × 11√3/2
x = 11√6/2
Answer:
remove the bracket on the other side by multiplying 180 by (2-n)
subtract 360 from 1260 to remain with -180n on the other side
divide both sides by -180n
then n become -5